1980
DOI: 10.1113/jphysiol.1980.sp013211
|View full text |Cite
|
Sign up to set email alerts
|

Arousal of a specific and persistent sodium appetite in the rat with continuous intracerebroventricular infusion of angiotensin II.

Abstract: SUMMARY1. Prolonged exposure of the brain of the normal Na-replete rat to angiotensin II produced a marked and persistent Na appetite. In a first series of experiments, short-term, repeated systemic injections of isoprenaline or renin (both of which raise circulating angiotensin levels), and repeated intracranial injections of angiotensin II evoked increased ingestion of 2-7 % NaCl. In the second series of experiments, continuous infusions of angiotensin II directly into the brain evoked extremely large intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
1
3

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(73 citation statements)
references
References 26 publications
4
65
1
3
Order By: Relevance
“…Preference for salt in rats was reported to be elicited by a variety of experimental interventions; adrenectomy, salivarectomy, ICV administration of angiotensin II, treatments with angiotensin-converting enzyme inhibitors, relatively high doses of deoxycorticosterone acetate, diuretics, and so forth. 2 In the enhancement of salt preference, peripherally, the salivary sodium concentration, which modulates the gustatory input to the central nervous system, and plasma aldosterone level, and centrally, the brain renin-angiotensin system (RAS) 27 may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Preference for salt in rats was reported to be elicited by a variety of experimental interventions; adrenectomy, salivarectomy, ICV administration of angiotensin II, treatments with angiotensin-converting enzyme inhibitors, relatively high doses of deoxycorticosterone acetate, diuretics, and so forth. 2 In the enhancement of salt preference, peripherally, the salivary sodium concentration, which modulates the gustatory input to the central nervous system, and plasma aldosterone level, and centrally, the brain renin-angiotensin system (RAS) 27 may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of angiotensin in sodium appetite is less clear. There is good evidence that angiotensin infused directly into the brain stimulates sodium appetite (Avrith & Fitzsimons, 1980;Bryant, Epstein, Fitzsimons & Fluharty, 1980). However, unless there is a coexisting hypovolaemia, presumably providing a neural signal to sodium appetite, circulating angiotensin seems rather ineffective at stimulating increased intake of NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that central administration of angiotensin II elicited a robust water intake that was followed by a modest salt appetite (Bryant et al, 1980;Buggy & Fisher 1974). Central administration of angiotensin II had also been shown to cause activation of oxytocinergic neurons in the hypothalamus (Ferguson & Kastings, 1988).…”
Section: Satiation and Inhibition Of Salt Appetitementioning
confidence: 99%